2003
DOI: 10.1128/jvi.77.16.8745-8755.2003
|View full text |Cite
|
Sign up to set email alerts
|

Stable High-Producer Cell Clone Expressing Virus-Like Particles of the Japanese Encephalitis Virus E Protein for a Second-Generation Subunit Vaccine

Abstract: We produced and characterized a cell clone (J12#26 cells) that stably expresses Japanese encephalitis virus (JEV) cDNA, J12, which encodes the viral signal peptide, premembrane (prM), and envelope (E) proteins (amino acid positions 105 to 794). Rabbit kidney-derived RK13 cells were transfected with a J12 expression plasmid, selected by resistance to marker antibiotics, and cloned by two cycles of a limiting-dilution method in the presence of antibiotics, a procedure that prevents the successful generation of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Changes in prM cleavage efficiency are known to affect the proportion of large and small flaviviral particles released from prMϩE-transfected cells (2,(23)(24)(25). Alterations in the proportion of virus particles were found in this study during the replication of several pr-M junction mutants.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Changes in prM cleavage efficiency are known to affect the proportion of large and small flaviviral particles released from prMϩE-transfected cells (2,(23)(24)(25). Alterations in the proportion of virus particles were found in this study during the replication of several pr-M junction mutants.…”
Section: Discussionmentioning
confidence: 69%
“…The majority of particles released from dengue virus-infected Vero cells and C6/36 mosquito cells are virion-sized particles (24,34). These large particles predominate in Japanese encephalitis virus (JEV)-infected Vero cell cultures, whereas subviral particles are more abundant in cultures of infected C6/36 cells (20,23,25,29). Both types of particles are equally common following infection of COS-1 cells with tick-borne encephalitis virus (TBEV) (1).…”
mentioning
confidence: 99%
“…Previous studies have shown that high level expression of VLPs could result in fusion, apoptosis, and death in some JEV susceptible cells (Kojima et al, 2003;Konishi et al, 2001). In this study, apoptosis induced by JEV VLPs was found in pCprME transfected 293FT cells, which suggested that the VLPs were also toxic for this cell line.…”
Section: Discussionmentioning
confidence: 52%
“…Cells expressing flavivirus prM and E proteins are known to secrete nucleocapsid-free subviral extracellular particles (EPs), which are similar to slowly sedimenting hemagglutinin (SHA) particles secreted from flavivirus-infected cells (47). EPs of JEV synthesized in mammalian expression systems have been evaluated for their immunogenicity and/or protective efficacy in mice (15,24,43). Two of these studies (24,43) demonstrated that the EPs induced neutralizing antibodies at levels comparable to those induced by an inactivated JE vaccine.…”
mentioning
confidence: 99%